Pemberdayaan Masyarakat Dusun Tanjung Mulyo, Desa Bumi Raya, Kecamatan Abung Selatan dalam Penanggulangan Sampah Anorganik - Ardianti, Indah Marlina; Pawhestri, Suci Wulan; Andandaningrum, Della; Ulmillah, Aulia (Universitas Muhammadiyah Surakarta, 2024)
The issue of inorganic waste management, particularly plastic, poses a significant challenge in Dusun Tanjung Mulyo, Desa Bumi Raya, Kecamatan Abung Selatan, Lampung Utara Regency, Lampung Province. This community service program aims to empower residents in managing inorganic waste through eco-brick production training. The methods employed include socialization, hands-on training, and participatory evaluation of the community’s skills in transforming plastic waste into valuable products. The results show a significant improvement in residents’ understanding and ability to sort waste and utilize plastic waste to create eco-bricks. Additional positive impacts include a reduction in indiscriminately discarded plastic waste and the formation of active community groups managing waste. Moreover, the eco-bricks produced offer economic potential for the residents, either for local construction purposes or as environmentally friendly building materials for sale. This program contributes to waste reduction and local economic empowerment and is expected to serve as a model for inorganic waste management in other regions.